Tolerance Biomarkers in Liver Transplantation: Independent External Validation of the Predictive Strength of SENP6 and FEM1C Gene Expression. Issue 9 (September 2019) - Pérez-Sanz, Fernando; Revilla-Nuin, Beatriz; Martínez-Alarcón, Laura; Herrero, José I.; Ramírez, Pablo; Pons, José A.; Baroja-Mazo, Alberto
Abstract : Background: Numerous studies have emphasized the genetic and phenotypic profiles of tolerant transplant patients. Moreover, different groups have defined several biomarkers, trying to distinguish patients who are going to be tolerant from those who are going to reject. However, most of these biomarkers have not been validated by other groups or even established for clinical practice. Methods: We reanalyzed and stratified the predictive capacity of 20 previously described biomarkers for liver transplantation tolerance in a cohort of 17 liver transplant patients subjected to an independent, nonrandomized, prospective study of immunosuppression drug withdrawal. Results: Only 4 of the 20 studied biomarkers (expression of SENP6, FEM1C, miR31, and miR95 ) showed a strong predictive capacity in the present study. miR31 and FEM1C presented an area under the ROC curve of 96.7%, followed by SENP1 with 93.3%. Finally, miR95 had an area under the ROC curve value <86.7%. Conclusions: Even though this independent analysis seems to confirm the predictive strength of SENP6 and FEM1C in liver transplantation tolerance, there are also risks in establishing biomarkers for clinical phenotypes without an understanding of how they are biologically relevant. Future collaborations between groups should be promoted so that the most promising biomarkers can be validated and implemented in daily clinical practice.